The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.05.07.083584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ascending dorsal column sensory neurons respond to spinal cord injury and downregulate genes related to lipid metabolism

Abstract: Regeneration failure after spinal cord injury (SCI) results in part from the lack of a pro-regenerative response in injured neurons, but the response to SCI has not been examined specifically in injured sensory neurons. Using RNA sequencing of dorsal root ganglion, we determined that thoracic SCI elicits a transcriptional response distinct from sciatic nerve injury (SNI). Both SNI and SCI induced upregulation of ATF3 and Jun, yet this response failed to promote growth in sensory neurons after SCI. RNA sequenci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 82 publications
3
3
0
Order By: Relevance
“…Our single cell approach does not allow recovery of many neurons and thus limits the depth of our neuronal analysis. However, our results support our previous studies showing that SCI and nerve injury elicits very distinct responses in sensory neurons 19 . Our results expand these findings and reveal that dorsal root crush leads to key RAG expression similar to nerve injury, suggesting that differential gene expression beyond RAGs and/or non-neuronal cells contribute to an axon generation speed that is half that of the peripheral nerve.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our single cell approach does not allow recovery of many neurons and thus limits the depth of our neuronal analysis. However, our results support our previous studies showing that SCI and nerve injury elicits very distinct responses in sensory neurons 19 . Our results expand these findings and reveal that dorsal root crush leads to key RAG expression similar to nerve injury, suggesting that differential gene expression beyond RAGs and/or non-neuronal cells contribute to an axon generation speed that is half that of the peripheral nerve.…”
Section: Discussionsupporting
confidence: 92%
“…We then determined the number of differentially expressed genes in six major cell types. Heat map of differential gene expression in the indicated cell types revealed that the magnitude of gene expression changes was the largest after SNC, but also occurred after DRC and SCI (Fig 1i), as previously suggested 19, 35 . We focused our analyses on neurons, endothelial cells, pericytes, Schwann cells, macrophages and SGC.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations